Ultrathin graphdiyne/graphene heterostructure as a robust electrochemical sensing platform - Sun, Xiuchao; Duan, Menglu; Li, Rongteng; Meng, Yuan; Bai, Qiang; Wang, Lina; Liu, Manhong; Yang, Zhugen; Zhu, Zhiling; Sui, Ning (American Chemical Society, 2022)
Graphdiyne (GDY) has been considered as an appealing electrode material for electrochemical sensing because of its alkyne-rich structure and high degrees of π-conjugation, which shows great affinity to heavy metal ions and pollutant molecules via d−π and π–π interactions. However, the low surface area and poor conductivity of bulk GDY limit its electrochemical performance. Herein, a two-dimensional ultrathin GDY/graphene (GDY/G) nanostructure was synthesized and used as an electrode material for electrochemical sensing. Graphene plays the role of an epitaxy template for few-layered GDY growth and conductive layers. The formed few-layered GDY with a high surface area possesses abundant affinity sites toward heavy metal ions (Cd2+, Pb2+) and toxic molecules, for example, nitrobenzene and 4-nitrophenol, via d−π and π–π interactions, respectively. Moreover, hemin as a key part of the enzyme catalytic motif was immobilized on GDY/G via π–π interactions. The artificial enzyme mimic hemin/GDY/G-modified electrode exhibited promising ascorbic acid and uric acid detection performance with excellent sensitivity and selectivity, a good linear range, and reproducibility. More importantly, real sample detection and the feasibility of this electrochemical sensor as a wearable biosensor were demonstrated.